Rethinking Retention: The Paradoxical Role of Reward, Recognition, and Job Satisfaction in Turnover Intention among Young Faculty in Chinese Private Universities - ChongFei, Shan; Aida Bt Samikon, Assoc. Prof Siti (Journal of Neonatal Surgery, 2025)
This study investigates the impact of reward and recognition on turnover intention among young academic staff in Chinese private universities, with job satisfaction examined as a mediating factor. Drawing on Herzberg’s Two-Factor Theory and Social Exchange Theory, a quantitative survey was conducted with 287 early-career faculty members. Structural equation modeling revealed that reward and recognition had a significant but unexpected negative effect on job satisfaction and a positive effect on turnover intention. Furthermore, job satisfaction was found to positively predict turnover intention, contrary to conventional expectations. Despite these findings, job satisfaction partially mediated the relationship between reward and recognition and turnover intention. These results highlight the complexity of faculty perceptions in resource-constrained educational settings, emphasizing that the perceived fairness and alignment of reward systems are critical. The study offers theoretical insights and practical recommendations for improving faculty retention strategies in China’s evolving private higher education landscape.